Pengaruh Implementasi Sistem Pengendalian Internal Pemerintah (SPIP) Terhadap Pengamanan Aset Tetap (Studi Kasus Pada Pemerintah Kabupaten Bekasi) - Deiana Suherlan; Vina Citra Mulyandani; Vita Citra (Indonesian Accounting Research Journal, 2022)
Fixed assets have a significant value in the Financial Statements and also can assist the government's operational activities in serving the community. The importance of these fixed assets shows that the security of fixed assets should be the main concern that must be pursued. Unfortunately, what happened in Bekasi regency government is not so. The findings of the Supreme Audit Agency in the Inspection Result Report for Bekasi Regency in 2020 show that there are still many unsafe fixed assets, such as fixed assets in the form of land that have not been supported by ownership certificates, recording of fixed assets that have not been good and the use of fixed assets that irresponsible. Therefore, to ensure asset security is required of the Government's Internal Control System. This research aims to determine the influence of the Government Internal Control System on the securing of fixed assets in the Bekasi Regency government. The research method used is descriptive quantitative method. The population in this study is the Regional Government Work Unit in the Bekasi Regency government, with the research sample being 32 Regional Apparatus Work Units and the number of respondents as many as 64 employees. Sources of data obtained from primary and secondary data. The data analysis method used a simple linear regression test with SPSS tools.